Liver Immunology Principles and Practice - Gershwin, M. Eric; Vierling, John M.; Manns, Michael P. (Humana Press : Imprint: Humana, 2007)
Immunology is a broad branch of biomedical science that covers the study of all aspects of the immune system in all organisms. It deals with, among other things, the physiological functioning of the immune system in states of both health and disease; malfunctions of the immune system in immunological disorders (autoimmune diseases, hypersensitivities, immune deficiency, allograft rejection); the physical, chemical and physiological characteristics of the components of the immune system in vitro, in situ, and in vivo. Immunology has various applications in several disciplines of science, and as such is further divided. Liver Immunology: Principles and Practice covers bacterial, parasitic and viral infections of the liver, autoimmune liver disease, alcoholic and nonalcoholic fatty liver diseases, and transplantation in an easy-to-read and thorough format. Authors also address the key issues that have arisen in this field in recent years, including physiological roles of hepatocytes, sinusoidal lining cells, activated macrophages (Kupffer cells), cholangiocytes and stellate cells, and their modulation of T cells, natural killer (NK) cells and NKT cells. This volume will become a must-read for clinicians, investigators and students, novice and expert alike.